Mindfulness as The Predictor of Online Impulsive Buying Tendency in Indonesian Early Adulthood - Natalie, Blanca; Ferdian, Flaviana Rinta (Jurnal Psikologi Teori dan Terapan, 2025)
Background: Online shopping attracts early adults (ages 20-39) due to price, convenience, time efficiency, etc, who are trying to regulate their shopping activities, and mindfulness is one approach can help individuals be aware of shopping behavior, avoiding impulsive buying. Objective: This study aims to examine whether mindfulness can significantly predict online impulsive buying tendency in early adults by using simple linear regression analysis, with early adults respondents (ages 20-39). Method: Research is using quantitative correlational design, and Pearson Correlation is used for analysis. Data (n=487) were collected using convenience sampling through online questionnaire containing Mindfulness Attention and Awareness Scale (MAAS-15) and Impulsive Buying Tendency Scale in the online shopping context (IBTS-20). Result: The results of the statistical analysis indicate mindfulness significantly and negatively predict online impulsive buying tendency in early adults. Additional analysis reveals a difference in the levels of females and males online impulsive buying tendency, with females scoring higher than males. Conclusion: Mindfulness predicts online impulsive buying tendency. Suggestion: Future research is suggested to explore other factors influence online impulsive buying tendency.   Keywords: Early adult; mindfulness; online impulsive buying tendency.   Abstrak Latar Belakang: Belanja online menarik perhatian dewasa awal (usia 20-39 tahun) karena faktor harga, kenyamanan, efisiensi waktu, dan lainnya. Mereka berusaha mengatur aktivitas belanja, dan mindfulness menjadi contoh pendekatan yang dapat membantu menyadari perilaku belanja mereka serta menghindari pembelian impulsif. Tujuan: Penelitian ini bertujuan untuk menguji apakah mindfulness dapat memprediksi kecenderungan pembelian impulsif online secara signifikan pada dewasa awal. Penelitian ini menggunakan metode kuantitatif dengan analisis regresi linier sederhana, dengan responden dewasa awal (usia 20-39 tahun). Metode: Penelitian ini menggunakan desain kuantitatif korelasional, dan analisis dilakukan dengan menggunakan Korelasi Pearson. Data (n=487) dikumpulkan menggunakan metode convenience sampling melalui kuesioner online berisi Mindfulness Attention and Awareness Scale (MAAS-15) dan Impulsive Buying Tendency Scale dalam konteks belanja online (IBTS-20). Hasil: Hasil analisis statistik menjelaskan mindfulness dapat secara signifikan dan negatif memprediksi kecenderungan pembelian impulsif online pada dewasa awal. Analisis tambahan menunjukkan perbedaan tingkat kecenderungan pembelian impulsif online antara perempuan dan laki-laki, dengan skor lebih tinggi pada perempuan. Kesimpulan: Mindfulness memprediksi pembelian impulsif online Saran: Penelitian selanjutnya disarankan untuk mengeksplorasi faktor-faktor lain yang mempengaruhi kecenderungan pembelian impulsif online.   Kata Kunci: Dewasa awal; kecenderungan pembelian impulsif online; mindfulness